2021
DOI: 10.3390/su13158519
|View full text |Cite
|
Sign up to set email alerts
|

University Graduate Students and Digital Competence: Are Future Secondary School Teachers Digitally Competent?

Abstract: Information and communication technology is very important both for teacher training and for delivering quality education. Therefore, university graduates must have a level of qualification in digital competencies suitable for their entry into the world of work. The research analyzes various aspects related to the use of technological resources by graduate students who were currently studying for a university master’s degree in compulsory secondary education, and the relationship between their use based on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…Various studies have investigated the acquisition of digital competence, teachers' digital competence perception, and examined the relationship between different dimensions [4,55,56]. This paper explores students' perceptions of their level of digital competence in the context of higher education, based on a case study of students at Gansu Agricultural University in Northwest China.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated the acquisition of digital competence, teachers' digital competence perception, and examined the relationship between different dimensions [4,55,56]. This paper explores students' perceptions of their level of digital competence in the context of higher education, based on a case study of students at Gansu Agricultural University in Northwest China.…”
Section: Discussionmentioning
confidence: 99%
“…Agile management in PES is supported by PES dedicated technology such as dedicated sport/training apps, mobile apps, gaming, VR, and AR courses/apps for training, and video conferences. Thus, teachers need to familiarize students with applications for sports training or physical education and try to stimulate the interest of students and athletes in PES by using games in the teaching process, such as GoNoodle [57]. Students can be stimulated to move with the help of video clips through which they learn a technical element and tactical structures or maintain their physical condition.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Greece, with 32 science teacher participants, it was revealed that 52% of the teachers had inadequate or weak use of technologies in their teaching practices with less than 19% of teachers making exceptional use of technology in their practice (Sofianidis & Kallery, 2021). University graduates within the teaching profession, do not have digital competencies nor the technical experiences to develop their students' technological skills using ICT (information and communications technology) (Pérez-Navío et al, 2021). Blackwell et al (2014), Karaca et al (2013) and Shiboko (2015) revealed that teachers with more years of teaching experience tend to have negative attitudes towards implementing technology in their classrooms, as opposed to teachers who have recently entered the profession.…”
Section: Content Knowledgementioning
confidence: 99%